Perbedaan Efektifitas Metode Terapi Akupresur Dan Hipnoterapi Terhadap Kualitas Tidur Pada Lanjut Usia Di Panti Wredha Kabupaten Banyumas - Taat Sumedi; Handoyo Handoyo; Wahyudi Wahyudi (Prodi Keperawatan Purwokerto, 2018)
Currently, prevalence of elderly people becomes high due to increasing life expectancy. One of the common problems of elderly people who live in nursing home is sleep disturbance. To deal with this problem, some alternative therapies for instance acupressure and hypnotherapy have indication to increase sleep quality of elderly people. The aim of this study was to investigate the effectiveness of acupressure and hypnotherapy towards sleep quality of elderly people at nursing home inBanyumas. This study was quasi experimental with nonequivalent control group pre dan post test design.The number of respondent was 40 and randomly assigned to either hypnotherapy group (n=20) or acupressure groups.(n=20). Their sleep quality was measured according to the Pittsburgh Sleep Quality Index (PSQI). Sleep quality was measured to both groups before treatment was performed. During three week after, hypnotherapy and acupressure ware treated to both hypnotherapy group and acupressure group respectively. In the last section, sleep quality was measured after treatments to both groups were finished. To analyze data, researcher occupied paired and independent t test to answer the research aims. However, normality of data were analysed previously before t test was performed by Kolmogorov Smirnov testThe results indicated significant differences in total PSQI scores before and after treatment for both hypnotherapy and acupressure group with p= 0.002 and 0,000 respectively. Furthermore, there is more effective of acupressure than hypnotherapy treatment in reducing PSQI score (increasing sleep quality) of elderly people with p = 0.000. Alternative therapies such as acupressure have positive impact in increasing sleep quality of elderly people in nursing home.